2015
DOI: 10.1097/olq.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Sexually Transmitted Disease Screening Among HIV-Infected Men Who Have Sex With Men Through Implementation of a Standardized Sexual Risk Assessment Tool

Abstract: Overall STD screening increases were observed after this intervention that included didactic training on the urgency of STD screening needs for HIV+ MSM, a presentation of preintervention clinic STD screening data, and the implementation of self-reported sexual risk assessment. Additional efforts are needed to determine feasible ways to accurately assess the appropriateness of STD screening and success of interventions to improve STD screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 11 publications
1
22
0
Order By: Relevance
“…Scarborough and colleagues developed a self-administered sexual risk assessment questionnaire. It was tested on a cohort of 364 HIV-infected MSM receiving care from a Kaiser Permanente HIV clinic [48]. Its implementation resulted in a relative increase in gonorrhea and chlamydia screening at any site by 26.8% (p=0.01) and a relative increase in syphilis testing by 18.8% (p=0.009) [48].…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
See 2 more Smart Citations
“…Scarborough and colleagues developed a self-administered sexual risk assessment questionnaire. It was tested on a cohort of 364 HIV-infected MSM receiving care from a Kaiser Permanente HIV clinic [48]. Its implementation resulted in a relative increase in gonorrhea and chlamydia screening at any site by 26.8% (p=0.01) and a relative increase in syphilis testing by 18.8% (p=0.009) [48].…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
“…It was tested on a cohort of 364 HIV-infected MSM receiving care from a Kaiser Permanente HIV clinic [48]. Its implementation resulted in a relative increase in gonorrhea and chlamydia screening at any site by 26.8% (p=0.01) and a relative increase in syphilis testing by 18.8% (p=0.009) [48]. An improvement in gonorrhea and chlamydia screening at each anatomical site was also reported, but only the increase pharyngeal testing was statistically significant [48].…”
Section: Interventions To Improve Hiv Care-based Sti Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an experiment that both educated providers about the importance of screening for gonorrhea, chlamydia, and syphilis and introduced a sexual risk assessment for patients resulted in significant increases in screening. 28 Automated structural changes, such as including a prompt in the electronic medical record to screen HIV-positive patients for STIs at regular intervals, could help to overcome a multiple barriers to routinization of the CDC's STI screening recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Northern California found that syphilis screening among HIV-infected patients significantly improved after provider training and the implementation of an STD-risk assessment [97]. In order to reach the goals of sufficient screening, additional clinician training appears to be necessary.…”
Section: Preventionmentioning
confidence: 99%